Faith in Access: Bridging Conversations between Religion and Disability - Anderson, Robert C. (Disability Studies Quarterly, 2006)
Disrupting barriers to access in the religious community may depend upon mutual engagement between the disability and religious communities. A respectful ambivalence between institutional religion and the disability community keeps this conversation at bay. Whether one is religious or not, engagement with the religious community is highly relevant to the disability community. The disability community's influence upon this large network of adherents could make a tremendous impact toward inclusion in society. This article provides an overview for disability scholars and advocates. The context for discussion is inclusion practices in the United States, with which the author is most familiar.